Analisa Pengaruh Arus Eksitasi terhadap Daya Reaktif Generator: Analysis The Effect of Excitation Current on Generator Reactive Power - Palit, Agnesia; Mangindaan, Glanny; Tulung, Novi (Universitas Sam Ratulangi, 2024)
Abstract — The output voltage changes at any time up or down will have an effect such as damage to generator components to overcome the instability of the voltage produced by the generator, a device is needed to regulate the excitation current, namely the Automatic Voltage Regulator (AVR) which works on the exciter, if the load decreases, the AVR will instruct the exciter to reduce the excitation current. A synchronous generator is an electrical machine that produces voltage and current (AC) by converting mechanical energy into electrical energy utilizing electromotive force (EMF). This study aims to analyze the effect of excitation current on generator reactive power. In this study, Lahendong Geothermal Power Plant uses an excitation system with brushes supplied by an excitation machine. Based on the data from the calculation of reactive power, the reactive power value obtained in the minimum of 3 samples is 2.96 MVAR, 2.97 MVAR, and 2.1 MVAR and at the same time the excitation current has increased by 15 Amperes so it can be concluded that the more reactive power increases, the excitation current also increases, therefore the excitation current will affect the value of the reactive power generated must be comparable. Keywords— Automatic Voltage Regulator; Excitation Current; Generator; Output Voltage; Reactive Power Abstrak — Tegangan keluaran berubah-ubah setiap saat naik atau turun akan memberikan dampak seperti kerusakan terhadap komponen generator dalam mengatasi ketidakstabilan tegangan yang dihasilkan generator diperlukan alat untuk mengatur arus eksitasi yaitu Automatic Voltage Regulator (AVR) yang bekerja pada eksiter, apabila beban berkurang maka AVR akan memerintahkan eksiter untuk mengurangi arus eksitasi. Generator sinkron merupakan mesin listrik yang menghasilkan tegangan dan arus (AC) dengan cara mengkonversikan energi mekanik menjadi energi listrik memanfaatkan gaya gerak listrik (GGL). Tujuan dari penelitian ini adalah untuk menganalisa pengaruh arus eksitasi terhadap daya reaktif generator. Pada penelitian ini PLTP Lahendong menggunakan sistem eksitasi dengan brush disuplai oleh mesin eksiter. Berdasarkan data hasil perhitungan daya reaktif didapat nilai daya reaktif yang diperoleh minimum dari 3 sampel sebesar 2.96 MVAR, 2.97 MVAR, dan 2.1 MVAR dan pada saat bersamaan arus eksitasi mengalami kenaikan sebesar 15 Ampere sehingga dapat disimpulkan bahwa semakin meningkat daya reaktif maka arus eksitasi juga meningkat, Oleh karena itu arus eksitasi akan mempengaruhi nilai daya reaktif yang dihasilkan harus sebanding. Kata kunci— Arus Eksitasi; Daya Reaktif; Generator; Pengatur Tegangan; Tegangan Keluaran